MonONTO - UMA PROPOSTA DE ONTOLOGIA DE MONITORAMENTO DE REDES E DE APLICAÇÕES AVANÇADAS DA INTERNET - Moraes, Priscilla Santos (2007)
Advanced applications on computer networks might require certain levels of Quality of Service (QoS); these requirements represent those applications' needs regarding the network. Levels of desired performance will be assured to the applications if the proper QoS requirements (those established in respective compliances) are satisfied. Users of these applications might wish to obtain information concerning the feasability of assuring these QoS requirements. The information can be provided by a specialist in network monitoring, or, if preferred, the user may access environments that supply the desired data; in this case, however, the user must possess the necessary technical knowledge in order to decipher the raw data, or in the form of charts and tables. Therefore, came the need to develop a system capable of making this information available to the user, in a friendly and intuitive way. The need to represent the knowledge of the computer network and advanced applications monitoring domain became imperative. The proposed solution includes the representation of the knowledge associated with the network and advanced applications monitoring domain. This way, expert systems are able to, without the interaction of network administrators, provide information to the users, in real time, about the network status and application performance, using a clear language, accessible to any level of users. Currently, few efforts to represent the knowledge related to the described domain - in order to make them machine processable - have been made. To represent the knowledge of the domain and the creation of the knowledge base that allows the knowledge to be used by an expert system a monitoring domain ontology was devised. This ontology will enable the formalization of the knowledge from network monitoring specialists, so that this knowledge can be processed by machines. The domain ontology, named MonONTO (Monitoring ONTOlogy for network measurement and advanced internet applications), facilitates the creation of the knowledge base for the domain, allowing specialized systems to infer and transmit high level information to the users. The implementation of MonONTO and an initial knowledge base, by choosing a language that formalizes the knowledge as it was specified by a number of standardization efforts in this area, was essential to validate the structure of terms and relationships that describe the domain. It was possible, by using proper tools, to derive the knowledge related to the domain, thus assuring that MonONTO closely reproduces the knowledge of the specialists. This document presents all the phases that comprised the idealization, definition, implementation and validation of MonONTO.